Tandem Solar Cells from Solution-Processed CdTe and PbS Quantum Dots Using a ZnTe-ZnO Tunnel Junction - Crisp, Ryan; Pach, Gregory F.; Kurley, J. Matthew; France, Ryan M.; Reese, Matthew O.; Nanayakkara, Sanjini U.; Macleod, Bradley A.; Talapin, Dmitri V.; Beard, Matthew C.; Luther, Joseph M. (Nano Letters, 2017)
We developed a monolithic CdTe-PbS tandem solar cell architecture in which both the CdTe and PbS absorber layers are solution-processed from nanocrystal inks. Due to their tunable nature, PbS quantum dots (QDs), with a controllable band gap between 0.4 and similar to 1.6 eV, are a promising candidate for a bottom absorber layer in tandem photovoltaics. In the detailed balance limit, the ideal configuration of a CdTe (E-g = 1.5 eV)-PbS tandem structure assumes infinite thickness of the absorber layers and requires the PbS band gap to be 0.75 eV to theoretically achieve a power conversion efficiency (PCE) of 45%. However, modeling shows that by allow-Rig the thickness of the CdTe layer to vary, a tandem with efficiency over 40% is achievable using bottom cell band gaps ranging from 0.68 and 1.16 eV. In a first step toward developing this technology, we explore CdTe-PbS tandem devices by developing a ZnTe-ZnO tunnel junction, which appropriately combines the two subcells in series. We examine the basic characteristics of the solar cells as a function of layer thickness and bottom-cell band gap and demonstrate open-circuit voltages in excess of 1.1 V with matched short circuit current density of 10 mA/cm(2) in prototype devices.
Keywords: Multifunction; photovoltaics; tandem; solar cell; quantum dots; nanoaystals